SISTEM PENYIRAMAN DAN PENGUSIR HAMA OTOMATIS PADA DAUN MINT BERBASIS MIKROKONTROLER ARDUINO UNO - Chusnul Chotimah; Kurnia Paramita Kartika (Universitas Islam Balitar, 2019)
Water requirements for mint / peppermint leaves are important so that mint / peppermint leaves grow and multiply well. Not only that, mint leaf protection from pests / insects is also important so that mint / peppermint leaves can live and have perfect leaf quality until harvest time. But in practice, humans are often negligent in watering and protecting pests on plants. To overcome these problems, mint / peppermint watering and automatic pest control use an arduino uno microcontroller as one solution. Automatic watering uses RTC as a schedule for minting and PIR sensors for detecting the movement of pests / insects approaching the mint leaves. The purpose of making this tool is to design hardware, software, and to find out the performance of an arduino uno microcontroller-based automatic watering pest control system. The making of this tool is based on arduino uno microcontoler combined with RTC (Real Time Clock) sensor and PIR (Passive Infrared) sensor. Here Arduino Uno as the main microcontroller, relay as a pump and fan switch, RTC as a regulator of mint leaves watering schedule, and PIR sensor to detect any movement of pests / insects that approach the mint leaves. Based on the results of the tests carried out, the automatic pest control and sprinkler system on the arduino uno microcontroller-based mint leaves has been successful. All programs run well according to the previous plan. And for the performance of mint leaves as a whole is in accordance with the established functions. For further research watering and repelling pests on mint leaves can automatically be added to the temperature sensor for use during the rainy season. Because in this study the tool is only used during the dry season.